Indonesia's food estate in context: Bridging past, present and future for national food security - Rahmad Supriyanto; Asmara Maharani; Aditya Alta (Center for Indonesian Policy Studies (CIPS), 2025)
Approximately 3.65 million hectares1 of peatlands and forest were cleared from the era of President Soeharto up to President Joko Widodo, primarily for the development of food estates. Another 3 million hectares of land are expected to be cleared to accommodate the food estate program during the current Prabowo-Gibran administration (Qodriyatun and Sawalman, 2024). The food estate initiative has been a top priority, aimed at securing national food security by boosting food crop production in Indonesia. A food estate in Indonesia is defined as a large-scale agricultural area that integrates the development of food commodities, horticulture, plantations, and livestock. Currently, according to Law No. 59/2024 on the National LongTerm Development Plan 2025-2045, the main objective of the food estate is to provide food reserves for national food security. This goal is respectable, but in practice food estate projects have been plagued with governance issues.
Keywords: 330